Asymmetries and hemispheric interaction in the auditory system of elderly people - Angenstein, Nicole (Frontiers in Neuroimaging, 2024)
Age-related changes of asymmetries in the auditory system and decreasing efficiency of hemispheric interaction have been discussed for some time. This mini-review discusses recent neuroimaging studies on alterations in lateralization of cortical processing and structural changes concerning the division of labor and interaction between hemispheres during auditory processing in elderly people with the focus on people without severe hearing loss. Several changes of asymmetries in anatomy, function and neurotransmitter concentration were observed in auditory cortical areas of older compared to younger adults. It was shown that connections between left and right auditory cortex are reduced during aging. Functionally, aging seems to lead to a reduction in asymmetry of auditory processing. However, the results do not always point into the same direction. Furthermore, correlations between function, anatomy and behavior in the left and right hemisphere appear to differ between younger and older adults. The changes in auditory cortex asymmetries with aging might be due to compensation of declining processing capacities, but at the same time these mechanisms could impair the balanced division of labor between the two hemispheres that is required for the processing of complex auditory stimuli such as speech. Neuroimaging studies are essential to follow the slow changes with aging as in the beginning no behavioral effects might be visible due to compensation. Future studies should control well for peripheral hearing loss and cognitive decline. Furthermore, for the interpretability of results it is necessary to use specific tasks with well-controlled task difficulty.